Pengaruh Penerapan Sistem Informasi Pemerintahan Daerah (SIPD) Terhadap Kualitas Laporan Keuangan Pada Pemerintah Kota Cimahi - Fiona Paat, Florencia; Abdullah Saleh, Suji (Indonesian Accounting Research Journal, 2023)
One of the initiatives issued by the central government to provide ease and empower the realisation of improvement information and data frameworks, financial data, and other government data for decision making is the implementation of the SIPD in all local government organisations in Indonesia, including the West Java Area, in particular within the Territorial Government of Cimahi City. The goal of this research is to ascertain how the implementation of the Sistem Informasi Pemerintahan Daerah (SIPD) has altered the standard of Cimahi City's monetary reporting. The purpose of this research was to examine SIPD Reverse's implementation in Cimahi City. A quantitative method was used to perform this study. This study's findings may represent a crucial piece of background knowledge. Methodology for gathering data by polling a representative sample of Cimahi's financial sector throughout the municipality. Analyses include the chi-square test, the t-test, the Friedman test, the Mann-Whitney U test, and the chi-squared test. According to the results, the Sistem Informasi Pemerintahan Daerah (SIPD) has a substantial effect on the accuracy of financial reporting.